Family- the Privileged Environment for the Child’s Development - Mocanu, Lacramioara (Didactica Danubiensis, 2023)
Family is considered the first environment, as well as the closest one to the child, in order to gain life experiences in their own rhythm of growing and developing. Through family, the child may establish a connection with the surrounding world, will exercise their senses, intelligence, convictions and attitudes, which will be polished within the extrafamilial social life.